Spectral Dependence of Photoregulation of Inorganic Nitrogen Metabolism in Chlamydomonas reinhardii - Azuara, María P. (1985)
The utilization of NO(3)(−) by green algae growing photoautotrophically under air, which are growth conditions close to their more habitual situations in nature, is associated with the excretion of NO(2)(−) and NH(4)(+) to the culture medium. The entire process is promoted by blue light and depends on photosynthetically active radiation for the required reducing equivalents. The stimulation of NO(3)(−) utilization and of its associated NO(2)(−) and NH(4)(+) excretions saturated at very low quantum fluxes of blue light (15 microequivalents per square meter per second) in Chlamydomonas reinhardii cells sparged with CO(2)-free air and irradiated with 50 microequivalents per square meter per second background red light. The wavelength dependence data of this stimulation correlated closely with the in situ photoactivation of nitrate reductase and also with the light induced increase in its biosynthesis and/or assembly. These results indicate that the photoregulation of inorganic N metabolism in C. reinhardii is mainly due to the blue light modulation of nitrate reductase. Although flavins are the most suitable candidates to act as physiological photoreceptors, the wavelength dependence data only show a major peak in the blue region between 400 and 500 nanometers.